1983
DOI: 10.1111/j.1365-2648.1983.tb00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursology of mouth care: preventing, comforting and seeking activities related to mouth care

Abstract: Mouth care across age groups, whether independently carried out or with assistance from a nurse, is frequently not considered in relation to the health of the mouth before commencement. This need for assessment and a schema as a baseline should dictate the most appropriate tools and the method of intervention. With a nursing model by Roper based on a model of living, nursing interventions are indicated across three age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…There is a large body of nursing literature concerning the oral assessment of hospital patients and long‐term care residents, as well as strategies for oral hygiene care provision and the maintenance of oral health 155,156,160–163,169,218,219,247–292 . Most of this literature comprises literature reviews and expert opinion; a few comprehensive literature/research reviews attempt to substantiate best‐practices in oral hygiene care for nurses.…”
Section: Resultsmentioning
confidence: 99%
“…There is a large body of nursing literature concerning the oral assessment of hospital patients and long‐term care residents, as well as strategies for oral hygiene care provision and the maintenance of oral health 155,156,160–163,169,218,219,247–292 . Most of this literature comprises literature reviews and expert opinion; a few comprehensive literature/research reviews attempt to substantiate best‐practices in oral hygiene care for nurses.…”
Section: Resultsmentioning
confidence: 99%
“…Maintenance of oral hygiene and provision of mouth care are considered basic but essential nursing interventions (5–9), especially for elderly institutionalized patients, who have higher levels of oral disease than those living at home (2, 10–15). However, several studies have shown that the provision of dental care for this group is inadequate (16), with treatment often sought only when patients experience pain or denture problems (14, 17).…”
mentioning
confidence: 99%
“…Thus, criterion validity for dental purposes was established. This instrument was substantially revised by Passos & Brand (1966) and subsequent authors have published modifications of Passos and Brand's instrument (Beck 1979, DeWalt 1975, Maurer 1977, Meissner 1980, Sorenson & Luckmann 1979, Speedie 1983, Van Drimmelin & Rollins 1969. By including ratings for other oral structures, these revisions have substantially reduced the variation in scores that may be attributed to plaque control.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Despite the staggering cost and widespread use of" these products, the manufacturers and the Food and Drug Administration in the USA have failed to supply references which support the efficacy of these products. The goals of nurse administered oral hygiene are implicit in the criteria defined in oral rating guides (Beck 1979, DeWalt 1975, Maurer 1977, Meissner 1980, Passos & Brand 1966, Sorenson & Luckmann 1979, Speedie 1983, Van Drimmelin & Rollins 1969. The implied goals are to maintain moisture, integrity and cleanliness of all oral tissue surfaces.…”
mentioning
confidence: 99%